Optional water development strategies for the Yellow River Basin: balancing agricultural and ecological water demands - Cai, Ximing; Rosegrant, Mark W. (American Geophysical Union, 2004)
The Yellow River Basin is of the utmost importance for China in terms of food production, natural resources management, and socioeconomic development. Water withdrawals for agriculture, industry, and households in the past decade have seriously depleted environmental and ecological water requirements in the basin. This study presents a modeling scenario analysis of some water development strategies to harmonize water withdrawal demand and ecological water demand in the Yellow River Basin through water savings and interbasin water transfers. A global water and food analysis model including the Yellow River Basin as one of the modeling units is applied for the analysis. The model demonstrates that there is little hope of resolving the conflict between agriculture water demand and ecological water demand in the basin if the current water use practices continue. Trade-offs exist between irrigation water use and ecological water use, and these trade-offs will become more intense in future years with population growth, urbanization, and industrial development as well as growing food demand. Scenario analysis in this study concludes that increasing basin water use efficiency to 0.67 first and then supplementary water availability by interbasin water transfer through the South-North Water Transfer Project may provide a solution to water management of the Yellow River Basin in the next 25 years.